Factors Influencing Development of Depressive Illness among Parkinson’s Disease Patients (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Depressive illness is present among Parkinson’s disease (PD) patients.Objective: The purpose of the present study was to see the influencing factors of development of depressive illness among Parkinson’s disease patients.Methodology: This comparative cross-sectional study was carried out in the Department of Neurology and Department of Psychiatry at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from July 2009 to June 2011 for a period of two (2) years. Parkinson’s disease patients who were attended at the movement disorder clinic and general OPD of Department of Neurology and in-patient department of Neurology at BSMMU, Dhaka were selected as study population. Patients with Parkinson’s plus syndrome, with dementia or other causes of parkinsonism like vascular or drug induced parkinsonism were excluded from this study. Data were collected by filling structured clinical questionnaire, then filling up of ‘structured clinical interview for DSM-IV Axis I disorders’ (SCID-CV) and self-reported ‘Depression scale` questionnaire. Parkinson disease was diagnosed by neurologist by the presence of two or more of the four cardinal criteria namely tremor, rigidity, bradykinesia and postural instability. Then patients were screened for depression by a psychiatrist of Department of Psychiatry at BSMMU, Dhaka.Result: A total of 100 Parkinson’s disease patients were interviewed and 80 patients ultimately participated in the study. The mean age of total Parkinson’s disease patients was 57.71±12.36 years ranging from 35 to 82 years with highest percentage (35%) had age group 65 years or above, 28.7% in 55 to 64 years, 22.5% in 45 to 54 years and lowest percentage (13.8%) in age group less than 45 years. Among 80 Parkinson’s disease patients, depression was present in 34 (42%) patients and was absent in 46 (58%) patients. Diabetes mellitus (p=0.125), hypertension (p=0.097), hypothyroidism (p=1.000), other illness (p=0.595), family history of PD (p=0.758) and levodopa use (p=0.661) were not significantly associated with the development of depressive illness in Parkinson’s disease.Conclusion: Diabetes mellitus (DM), hypertension (HTN), hypothyroidism, other illness, family history of PD and levodopa use do not significantly influence in the development of depressive illness among the Parkinson’s disease.Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 106-110